Product and Process Design : Driving Sustainable Innovation - Harmsen, Jan; De Haan, Andre B.; Swinkels, Pieter L. J. (Boston : De Gruyter, 2024)
Product and process design - driving sustainable innovation" is the 2nd edition of a comprehensive textbook for product and process design courses at BSc, MSc, EngD, and PhD level. It covers both heuristics based design methods as well as systems engineering approaches. It contains specific methods to co-design products and processes, so that both designs are better than when these designs are made separately. This integrated combination makes the book unique. For making designs that contribute to the Sustainable Development Goals of the United Nations specific methods are provided for the People, Planet, and Prosperity dimensions. This second edition of the book includes examples and exercises for each design method, which makes it very suitable for teaching purposes. The book is furthermore of interest to industrial process and product developers for many industry branches as it provides methods for design, modelling, and experimental validation for each innovation stage. It is also very useful for R&D managers as it provides guidelines for essential activities in each innovation stage (discovery, concept, feasibility, development, detailed engineering), leading to successful implementations of new processes and new products.
Includes Index
Keywords: Product design; Engineering design; Sustainable development